Warfarin resumption following anticoagulant-associated intracranial hemorrhage: A systematic review and meta-analysis. Issue 160 (December 2017) - Chai-Adisaksopha, Chatree; Iorio, Alfonso; Hillis, Christopher; Siegal, Deborah; Witt, Daniel M.; Schulman, Sam; Crowther, Mark
Abstract: Background: This study aims to assess the effect of warfarin resumption in patients who experienced warfarin-associated intracranial hemorrhage (ICH). Methods: We conducted a systematic review and meta-analysis of studies evaluating the outcomes of adult patients who survived warfarin-associated ICH. We included studies that compared patients who resumed warfarin versus those who did not. Results: Of 3145 studies screened, ten observational studies were included in the final analysis. Death occurred in 181 of 968 patients (18.7%) who resumed warfarin and 834 of 2579 (32.3%) who did not resume warfarin (RR 0.51, 95% CI 0.34 to 0.76, P = 0.0009). Ischemic stroke occurred in 32 of 902 (3.5%) patients who resumed warfarin and 172 of 2467 (7.0%) patients who did not resume warfarin (RR 0.56, 95% CI 0.39 to 0.82, P = 0.002). Venous thromboembolism occurred in 4 of 224 (1.8%) patients who resumed warfarin and of 33 of 681 (4.8%) patients who did not resume warfarin (RR 0.39, 95% CI, 0.15 to 1.03, P = 0.06). Recurrent ICH occurred in 200 of 2994 (6.7%) patients who resumed warfarin and 358 of 4652 (7.7%) patients who did not resume warfarin (RR 0.89, 95% CI 0.65 to 1.23, P = 0.49). Conclusion: The study suggests that warfarin resumption is associated with significant reduction in ischemic stroke and venous thromboembolism when compared to no warfarin resumption in patients who experience warfarin-associated ICH. Although these results are strongly supportive of restarting anticoagulation, prospective studies are required to confirm our results due to the high likelihood of bias in the included studies. Highlights: Patients who presented with warfarin associated intracranial bleeding were at risk of thromboembolic event and recurrent intracranial bleeding Warfarin resumption was associated significant reduction of all-cause mortality and ischemic stroke. Recurrent intracranial bleeding was not significantly increased in patients who resumed warfarin as compared to those who did not.